INTEGRATING THE FULL RANGE LEADERSHIP MODEL IN VIETNAM’S PHARMACEUTICAL INDUSTRY: A SYSTEMATIC REVIEW OF CULTURAL AND ORGANISATIONAL FIT - Do, Anh Thu; Mazumdar, Anupam (International Journal of Engineering Science Technologies, 2025)
The Vietnamese pharmaceutical industry has rapidly evolved into one of Southeast Asia’s most dynamic markets, driven by economic growth, healthcare demand, and global integration. With this expansion comes a critical need for effective leadership models that align with both organisational objectives and deeply rooted cultural values. This paper systematically reviews leadership theories with a particular focus on the Full Range Leadership Model (FRLM) to assess its applicability and integration into the Vietnamese pharmaceutical sector. Drawing from transformational, transactional, and laissez-faire leadership paradigms, the FRLM provides a comprehensive framework to navigate the industry’s operational and strategic challenges. This review identifies the strong alignment between transformational and servant leadership styles and Vietnam’s collectivist, hierarchical culture, which emphasises harmony, respect for authority, and long – term relationships. Conversely, transactional leadership is recognised for ensuring operational compliance and structure, particularly within supply chain and quality assurance processes. Laissez – faire leadership, while potentially fostering autonomy, is cautioned against due to the high stakes of regulatory compliance and safely in pharmaceuticals. The paper synthesises a breadth of scholarly and industry sources, revealing that most Vietnamese pharmaceutical firms are adopting hybrid leadership approaches that combine motivational and performance – driven styles. Recommendations are provided for leadership development programs that reflect Vietnam’s cultural context while embracing global standards and innovative practices. The paper concludes that the FRLM – particularly its transformational and transactional dimensions hold significant potential to enhance leadership effectiveness, workforce satisfaction, and industry sustainability.